Incidences sémantiques de la suffixation sur la réduplication verbale en wolof - Augustin NDIONE (Corela)
In Wolof, conjugation is realized using an invariable lexical basis to which are attached affixes carrying marks of IPAM (e.g. in French : Indice ; Personne ; Aspect-Temps ; Mode) (Perrin 2005 : 22) and highlighting semantic and grammatical roles. Reduplication is productive at several lexical categories (nouns, verbs, adverbs). As verbal derivation is mostly built by both reduplication and suffixation, I propose here to analyze and describe the relationship in the construction of meaning between these two processes.